1997
DOI: 10.1111/j.1600-0714.1997.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 gene mutations and HPV infection in primary head and neck squamous cell carcinomas do not correlate with overall survival: a long term follow‐up study

Abstract: We analyzed specimens of head and neck squamous cell carcinomas (HNSCC) from 110 patients for p53 gene mutations, and 92 of them for human papillomavirus (HPV) infection, in order to evaluate the prognostic significance of these factors by comparison with clinical follow-up data. Mutations within the exons 5 to 8 of the p53 gene were found in 48 tumors (44%). Sequencing revealed in most cases mis-sense mutations (16/21). Frequency of p53 gene mutations was not related to the tumor stage or the presence of lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 29 publications
5
46
2
Order By: Relevance
“…The largest studies evaluating HPV DNA detection of in lip SCC was a multicenter study held in Sweden, Norway and Finland, which included 57 cases and found 4% DNA HPV positive, in a population greatly different from of latin american 35 . Detection rate of HPV DNA similar to present work was found by Riethdorf 15 that evaluated 18 cases of lip SCC by PCR using frozen tissues and found 50% of positivity.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The largest studies evaluating HPV DNA detection of in lip SCC was a multicenter study held in Sweden, Norway and Finland, which included 57 cases and found 4% DNA HPV positive, in a population greatly different from of latin american 35 . Detection rate of HPV DNA similar to present work was found by Riethdorf 15 that evaluated 18 cases of lip SCC by PCR using frozen tissues and found 50% of positivity.…”
Section: Discussionsupporting
confidence: 75%
“…This lack of association between HPV infections and these variables was also observed in other studies 15,36 . We believe that the lip can be only a reservoir for the human papillomavirus.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…p53 and HPV-HR have been examined in association with HNC prognosis with conflicting results observed (19). Overexpression of p53 was related to worse prognosis in some investigations (3,5,20) but not in others (4,17), whereas HPV-HR has been associated with better prognosis (7,21). Studies of cervical cancer have not been able to address the p53/HPV relationship with survival because HPV-HR is a necessary cause of these tumors and thus cannot serve as a model for predicting outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HNC patients show low survival (50%) and high recurrence rates (25%; refs. 7,12,[16][17][18]. p53 and HPV-HR have been examined in association with HNC prognosis with conflicting results observed (19).…”
Section: Introductionmentioning
confidence: 99%